(untitled) (International Journal of Engineering and Computer Science, 2013)
Heterogeneous catalyst of transesterification is gaining more support because of the friendly nature of the catalysts, easy separation from the products, their reusability and less process water require. This paper present the efficacy of some of the common solid catalysts for biodiesel production. Many researchers have developed different solid base/acid catalysts for transesterification of vegetable oil in order to replace the conventional homogeneous catalysts that have a lot of limitations. The performances of some of these heterogeneous catalysts with appropriate vegetable oils are reviewed in this paper. K/KOH/ϒ.Al2O3 has yielded 84.5% biodiesel from rapeseed oil, X/Y/MgO/ϒ. Al2O3 yielded 96.1% biodiesel from jatropha curcas oil, SO4/TiO2.nH2O and SO4/Zr(OH)2 yielded 90% biodiesel from cotton seed oil. CaO, SrO, Ca(OCH3)2 and Ca(OCH2CH3)2 yielded 95% biodiesel from soybean oil. ZnO, 2 2 4 SO / SnO - /, and 2 2 4 SO / ZrO - have good yield of biodiesel with palm kernel oil and coco nut oil. Heterogeneous catalysis is a process intensification.